2010
DOI: 10.1002/cncr.25280
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of the combination of rituximab, fludarabine, and mitoxantrone for rituximab‐naive, recurrent/refractory follicular non‐Hodgkin lymphoma with high tumor burden

Abstract: BACKGROUND: This phase 2 trial was undertaken to evaluate the efficacy and safety of rituximab combined with intravenous fludarabine and mitoxantrone (R-FM) for patients with recurrent/refractory follicular lymphoma who had high tumor burden according to Groupe d'Etude des Lymphomes Folliculaires (GELF) criteria. METHODS: Fifty patients were enrolled who had received a maximum of 2 previous regimens, including 1 cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP)/CHOP-like regimen but no previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…High clinical efficacy was observed with the R-FM induction regimen with 100% overall response rate (ORR) and high CR rates (66%). 5,6 The study cohort was too small to observe the inferior OS recently reported by several study groups. [21][22][23] Previous data on rituximab PK in follicular lymphoma were mainly generated during monotherapy.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…High clinical efficacy was observed with the R-FM induction regimen with 100% overall response rate (ORR) and high CR rates (66%). 5,6 The study cohort was too small to observe the inferior OS recently reported by several study groups. [21][22][23] Previous data on rituximab PK in follicular lymphoma were mainly generated during monotherapy.…”
Section: Discussionmentioning
confidence: 97%
“…[2][3][4] Fludarabine-mitoxantrone combinations have shown strong debulking activity as initial therapy followed by rituximab maintenance. 5,6 While rituximab maintenance with a standard dose of 375 mg/m 2 prolongs clinical remissions, administration schedules still vary: 3-monthly infusions for two years and 2-monthly infusions for one or two years are those most frequently used. 4,7 Some pharmacokinetic data for rituximab have been reported for induction treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In a Phase II study conducted by Morschhauser et al, 50 patients with refractory/relapsed HTB FL received R-FM and showed a 3-yr PFS of 47% and 3-yr OS of 66%; 72% of patients presented neutropenia G3 which was complicated in 14% of these by an infection. Secondary tumors were observed in three patients (two cutaneous tumors and one case of chronic lymphocytic leukemia), but no case of secondary myelodysplasia was recorded [82].…”
Section: Other Alkylating Agent-based Regimensmentioning
confidence: 93%
“…The ORR was of 84% (uCR/CR 68%), achieving the best response at the end of fourth course of R-FM. After a median follow-up of 4 years, 56% of patients relapsed or died, with a median PFS and event-free survival of 33 and 26 months, respectively [82]. Other regimens cited above are also to be considered in second relapse, as bendamustine, mitoxantrone or platinum-containing regimens, as gemcitabine with oxaliplatin (Gem/Ox regimen).…”
Section: Treatment In Second and Further Linesmentioning
confidence: 99%
“…Adverse prognostic factors in FL include a high (≥3) FL International Prognostic Index (FLIPI) score, representing patients aged >60 years, and/or with stage III–IV disease, anemia, >4 involved nodal areas, and/or elevated lactate dehydrogenase (LDH) [7,10,11], which has been validated in the first-line setting [11] and shown to have prognostic value at first relapse [10]. In addition, another indicator of poor prognosis is a high tumor burden by modified Groupe d’Etude des Lymphomas Folliculaires (GELF) criteria [12], which includes involvement of ≥3 nodal sites of ≥3 cm diameter, any nodal/extranodal tumor mass of ≥7 cm diameter, splenomegaly, pleural effusion or peritoneal ascites, leukocytes <1.0 x 10 9 /L, or platelets <100 x 10 9 /L [12,13]. …”
Section: Introductionmentioning
confidence: 99%